Social & Legal Perspectives on Underuse of Medication-Assisted Treatment for Opioid Dependence - Andraka-Christou, Barbara (2016)
Medication-assisted treatment (MAT) in combination with counseling is considered the most effective treatment for opioid dependence by the World Health Organization, U.S. Department of Health and Human Services, and American Society of Addiction Medicine. Two MAT medications, buprenorphine and methadone, are considered essential medicines by the World Health Organization. Despite MAT’s effectiveness, it is severely underused in U.S. treatment settings, including physicians’ offices, hospitals, the Veterans Administration, residential treatment centers, prisons, and drug courts. The dissertation examines social and legal reasons for under-use of MAT in the U.S., including dominance of abstinence-only treatment methods, separation of addiction treatment from mainstream medical treatment, insurance barriers, statutory and regulatory barriers, under-education of physicians in addiction medicine, under-education of mental health counselors in MAT, lack of physician involvement in the criminal justice system, and public understanding of addiction as a spiritual disease rather than a brain disease. The dissertation concludes with suggestions for expanding access to MAT, including government funding incentives and integration of MAT into existing addiction treatment centers and educational programs